2021
DOI: 10.1177/12034754211053310
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Skin Manifestations in Skin of Colour

Abstract: Coronavirus disease (COVID-19) skin manifestations have been increasingly reported in medical literature. Recent discussions have identified a lack of images of skin of color (SOC) patients with COVID-19 related skin findings despite people with skin of color being disproportionately affected with the disease. There have been calls to prioritize the identification of COVID-19 skin manifestations in patients with SOC and disseminate these findings. The objective of this article is to review the existing literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(41 citation statements)
references
References 50 publications
2
37
0
2
Order By: Relevance
“…39 Notably, these disparities increased when rates of hospitalization and death were considered. 39 Despite this, there has been a Kawasaki-like clinical presentation in pediatric patients 22 Majority developed fever prior or concurrently with mucocutaneous fi ndings 22 Cutaneous fi ndings not correlated with more severe clinical course 22 Patients tend to be older and have more gastrointestinal symptoms than in Kawasaki disease 22 Non-White patients [17][18][19][20][21]23,24 Small reports of decreased rates of specifi c COVID-19 skin fi ndings 23,24 Scalp involvement and telogen effl uvium may be more common [17][18][19][20] Hyperpigmentation may provide insight into previous infl ammatory process 21 No defi nitive data comparing outcomes based on cutaneous fi ndings…”
Section: Non-white Populationsmentioning
confidence: 99%
See 3 more Smart Citations
“…39 Notably, these disparities increased when rates of hospitalization and death were considered. 39 Despite this, there has been a Kawasaki-like clinical presentation in pediatric patients 22 Majority developed fever prior or concurrently with mucocutaneous fi ndings 22 Cutaneous fi ndings not correlated with more severe clinical course 22 Patients tend to be older and have more gastrointestinal symptoms than in Kawasaki disease 22 Non-White patients [17][18][19][20][21]23,24 Small reports of decreased rates of specifi c COVID-19 skin fi ndings 23,24 Scalp involvement and telogen effl uvium may be more common [17][18][19][20] Hyperpigmentation may provide insight into previous infl ammatory process 21 No defi nitive data comparing outcomes based on cutaneous fi ndings…”
Section: Non-white Populationsmentioning
confidence: 99%
“…Palpation can be identify cutaneous eruptions when erythema is subtle 21 Messenger RNA COVID-19 vaccines 9,12,[25][26][27][28] Acute and delayed local reactions most commonly seen, followed by urticarial and morbilliform eruptions 9 Median time to onset after fi rst dose was 7 days, occurring in 2 clusters between day 1-3 and day 7-8 9 Shorter median time from second dose, occurring at day 19…”
Section: Non-white Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Much of the literature and imaging available today surrounding COVID-19 and cutaneous manifestation is on lighter skin, with little representation of skin of color [ 70 , 71 ]. This is despite the fact that individuals with skin of color are disproportionately affected by COVID-19 [ 72 , 73 ]. Early in the pandemic, Lester et al reported that of publications on COVID-19 and dermatology, 91% of images involved white patients and 9% were Hispanic, with no representation of cutaneous manifestations in dark skin [ 74 ].…”
Section: Cutaneous Reactions To Sars-cov-2 Infectionsmentioning
confidence: 99%